Relationship Between Exercise Habits and Stress Levels in Students of Non-Sport Study Program - Sultan Najmi Kurnida; Rahayu, Setya (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to analyze the relationship between exercise habits and stress levels in non-sports study program students at Universitas Negeri Semarang. The study used a quantitative design with a descriptive correlational approach and a cross-sectional design. The sample consisted of 50 active students of the Faculty of Medicine who were selected purposively. Data was collected through an exercise habit questionnaire (IPAQ-SF) and a Perceived Stress Scale (PSS-10), then analyzed using the Spearman Rank test. The results showed that most respondents had moderate (80%) and high (20%) physical activity levels, without a low category. The average stress score was 20.12, indicating a moderate category, with 50% of students experiencing moderate stress and 28% experiencing high stress. There was a strong and significant negative relationship between total physical activity and stress levels (ρ = -0.804; p <0.01), especially heavy activity which showed a stronger correlation (ρ = -0.825; p <0.01). In contrast, moderate activity and walking did not show a significant relationship with stress. This study concluded that the intensity of physical activity, especially vigorous exercise, plays an important role in reducing stress levels of non-sports students. These results are expected to be the basis for campuses in designing mental health programs based on physical activity.